GrpE Immunization Protects Against Ureaplasma urealyticum Infection in BALB/C Mice - Tang, Yanhong; Guo, Fangyi; Lei, Aihua; Xiang, Jing; Liu, Pengqin; Ten, Wenyou; Dai, Guozhi; Li, Ranhui (Frontiers in Immunology, 2020)
Nucleotide exchange factor (GrpE), a highly conserved antigen, is rapidly expressed and upregulated when Ureaplasma urealyticum infects a host, suggesting that, if it induces an anti-U. urealyticum Th1 immune reaction, it could act as a candidate vaccine. Here, we evaluated the potential of recombinant GrpE protein to protect against U. urealyticum genital tract infection in a mouse model. Recombinant GrpE induced a humoral and cellular immune response after intramuscular injection of BALB/C mice. Total IgG production increased in response to GrpE protein, with IgG2a levels being higher than IgG1. GrpE-immunized mice produced a T-lymphocyte response after re-stimulation with immunogen GrpE in vitro, which showed a Th1-biased cytokine spectrum with high levels of IFN-γ. Mice inoculated with U. urealyticum showed a significantly reduced bacterial burden in cervical tissues after immunization with GrpE. Histopathological analysis confirmed that tissues of GrpE-immunized BALB/C mice were protected against the pathological effects of U. urealyticum infection. In conclusion, this study reveals GrpE protein as a promising new candidate vaccine for preventing U. urealyticum reproductive tract infection.